Cladophialophora bromeliacearum (Herpotrichiellaceae, Chaetothyriales), a novel endophytic species from the Brazilian tropical dry forest - Nascimento, Sandy S.; Ferro, Layanne O.; Freire, Karla T.l.s.; Barbosa, Renan N.; Paiva, Laura M.; Souza-Motta, Cristina M.; Bezerra, Jadson D.p. (Phytotaxa, 2021)
Two isolates of fungal endophytes were obtained from the leaves of Tillandsia catimbauensis (Bromeliaceae) in the Brazilian tropical dry forest (Caatinga), according to their morphology, they were previously identified as Phialophora-like fungi. On the basis of phylogenetic analysis using ITS and LSU rDNA sequences, along with morphological features, these isolates are here described as Cladophialophora bromeliacearum sp. nov. The new species is morphologically characterized by Phialophora-like conidiogenous cells, subspheric to ellipsoid conidia, and the production of chlamydospores in culture.